2023
DOI: 10.15575/rjsalb.v7i1.24250
|View full text |Cite
|
Sign up to set email alerts
|

Nature Harmony and Local Wisdom: Exploring Tri Hita Karana and Traditional Ecological Knowledge of the Bali Aga Community in Environmental Protection

Abstract: Environmental pollution has evolved into a global issue that affects all humans can feel. The most frequent cause is a massive land conversion that neglects the negative effects on the surrounding environment. The Bali Aga indigenous people in Trunyan and Tenganan villages have optimism about preventing a global ecological crisis by maintaining their customary forests. This study examines how the Bali Aga Indigenous people in Trunyan and Tenganan villages maintain their traditional ecological knowledge (TEK), … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 16 publications
1
4
0
Order By: Relevance
“…These constructions are basic and cost-effective, demonstrating MARRS's pragmatic approach. This strategy is consistent with the Palemahan principle of the Tri Hita Karana philosophy, which calls for responsible resource management (Qodim, 2023). The utilization of MARRS also fits in with the greater objectives of the joint endeavor.…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…These constructions are basic and cost-effective, demonstrating MARRS's pragmatic approach. This strategy is consistent with the Palemahan principle of the Tri Hita Karana philosophy, which calls for responsible resource management (Qodim, 2023). The utilization of MARRS also fits in with the greater objectives of the joint endeavor.…”
Section: Resultssupporting
confidence: 73%
“…This initiative teaches participants how to adopt and securely attach coral fragments onto binding media, which are subsequently placed on the seabed at Mengiat Beach, as a Marine Protected Area (MPA). This hands-on training connects strongly with the Tri Hita Karana philosophy's Pawongan principle, which emphasizes harmonious social interactions and community-centered strategies (Qodim, 2023). This approach enhances the ecological integrity of the maritime environment by encouraging people and communities to actively contribute to coral preservation, as it has been shown by Assa & Adirinekso (2022), who found that in order to prevent coral reef destruction, which has an impact on people's livelihoods, the community has carried out conservation measures in Ujung Genteng, Sukabumi, by involving diverse stakeholders.…”
Section: Preparationmentioning
confidence: 89%
See 3 more Smart Citations